2010
DOI: 10.1016/j.jvs.2010.04.024
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative platelet and monocyte activation in patients with critical limb ischemia

Abstract: Patients undergoing surgery for CLI have the highest level of in vivo platelet and monocyte activation, and these persist throughout the perioperative period. Additional antiplatelet therapy may be of benefit in protecting vascular patients with more severe disease during this period of increased risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 33 publications
1
16
1
Order By: Relevance
“…Another limitation is the fact that blood samples were drawn from the arterial sheath, which may potentially dilute any local effect caused by the FFR-positive lesion. Systemic blood sampling may not recognize local PLC formation in the coronary circulation, although previous research have also found differences in PLCs in systemic blood samples of patients with localized arterial pathology [9], [29].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Another limitation is the fact that blood samples were drawn from the arterial sheath, which may potentially dilute any local effect caused by the FFR-positive lesion. Systemic blood sampling may not recognize local PLC formation in the coronary circulation, although previous research have also found differences in PLCs in systemic blood samples of patients with localized arterial pathology [9], [29].…”
Section: Discussionmentioning
confidence: 90%
“…Increased systemic platelet reactivity was described in patients with documented coronary artery disease immediately after peak exercise [27]; [28], however no relationship with ischemia was found [27]. In critical limb ischemia, increased PMCs and expression of P-selectin was observed, implying an ischemic mechanism of platelet activation [29]. Conversely, other investigators found an inverse relationship between coronary obstruction and platelet reactivity [30], although all patients investigated had severe single-vessel disease.…”
Section: Discussionmentioning
confidence: 95%
“…Local ischemic preconditioning attenuates platelet activation and aggregation (182). In humans, marked systemic platelet activation has been demonstrated in patients with acute coronary syndromes (183) or acute limb ischemia (184). In animal models, the extent of platelet activation is related to the extent of subsequent tissue injury after reperfusion (185).…”
Section: Clinical Evidence For Ricmentioning
confidence: 99%
“…MPAs are increased in numerous conditions associated with ischemia and thrombosis, such as acute MI, 7,15 limb ischemia, 16 and stroke. 17 However, an interaction between monocytes (and their individual subsets) and platelets has not been studied in HF, and the possible impact on clinical outcome is unknown.…”
Section: Clinical Perspective On P 135mentioning
confidence: 99%